Modeling of linear parameter-varying systems using interpolation of root macromodels and scaling coefficients. (August 2015) - Ferranti, Francesco; Rolain, Yves
Abstract: In this paper, we propose a methodology for the modeling of linear parameter-varying systems which is based on an innovative interpolation approach at the transfer function level with scaling coefficients. This interpolation approach is different from standard interpolation of state-space matrices for the modeling of linear parameter-varying systems. The proposed method starts from a discrete set of frequency-domain data samples of the system transfer function for fixed values of the scheduling parameters. Then, a rational system identification step is used to generate the root macromodels . Finally, an innovative interpolation approach at the transfer function level with scaling coefficients is used to build the linear parameter-varying representation. Pertinent numerical results validate the proposed linear parameter-varying modeling technique. Abstract : Highlights: We propose a novel modeling method for linear parameter-varying systems. Root macromodels, scaling coefficients and interpolation schemes are used. This method is different from direct interpolation of state-space matrices. Numerical results confirm the accuracy and robustness of the proposed modeling method.